Comparison of the Ratio of the Lenght of the Second and Fourth Digits in Subgroups of Fertile and Infertile Cases - Akinsal, Emre Can; Demirtas, Abdullah; Ekmekcioglu, Oguz (Urology Journal, 2017)
Purpose: To identify any relationship between known reasons of male infertility and 2D:4D ratio. Materials and Methods: A total of 371 males were included in the study. The cases were grouped into 6 groups including sperm count < 5 million/mL, sperm count ≥ 5 million/mL, Klinefelter Syndrome, hypogonadotropic hypogonadism, vasal agenesis and control. Groups were compared with each other in terms of 2D:4D ratios and groups with a 2D:4D ratios below 1 and equal/above 1 were compared. Results: The greatest ratios were in the vasal agenesis and hypogonadotropic hypogonadism groups and analysis of the data with logistic regression analysis showed that there was a significant difference in terms of 2D:4D ratios for these groups when comparing with control group. The other groups showed no statistically significant differences. Conclusion: The results of the present study showed some significant difference between 2D:4D ratios for the subgroups of the fertile and infertile cases. Although, 2D:4D ratio is not an unaccompanied parameter to reveal causes of male infertility, it can be associated with some situations that are related with male infertility.